2011
DOI: 10.1161/strokeaha.111.622134
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Disadvantage and Ischemic Stroke

Abstract: Background and Purpose Neighborhood characteristics may influence the risk of stroke and contribute to socioeconomic disparities in stroke incidence. The objectives of this study were to examine the relationship between neighborhood socioeconomic status (NSES) and incident ischemic stroke and examine potential mediators of these associations. Methods We analyzed data from 3834 whites and 785 African Americans enrolled in the Cardiovascular Health Study, a multicenter, population-based, longitudinal study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 35 publications
1
67
1
Order By: Relevance
“…28 Blacks are also at a disadvantage for environmental and neighborhood exposures that are related to stroke risk, including an alarmingly disproportionate number living in poverty, one of the strongest risk factors for stroke as well as other CVD outcomes. 29, 30 Much work remains to continue to document non-traditional risk factors that are related to stroke where Blacks are at a disadvantage for prevalence or severity of the risk factor, so that interventions and policies can address them. Measurement error and residual confounding: All regression models (including both the proportional hazards and logistic models employed here) assume that the predictor variables are measured with precision. For the predictor variables in this analysis (age, race and sex), it is reasonably safe to assume that this is not a major issue.…”
Section: Discussionmentioning
confidence: 99%
“…28 Blacks are also at a disadvantage for environmental and neighborhood exposures that are related to stroke risk, including an alarmingly disproportionate number living in poverty, one of the strongest risk factors for stroke as well as other CVD outcomes. 29, 30 Much work remains to continue to document non-traditional risk factors that are related to stroke where Blacks are at a disadvantage for prevalence or severity of the risk factor, so that interventions and policies can address them. Measurement error and residual confounding: All regression models (including both the proportional hazards and logistic models employed here) assume that the predictor variables are measured with precision. For the predictor variables in this analysis (age, race and sex), it is reasonably safe to assume that this is not a major issue.…”
Section: Discussionmentioning
confidence: 99%
“…In an Australian study, 15 for example, arealevel deprivation was associated with obesity and smoking, although no statistically significant association was apparent with diabetes mellitus, at-risk alcohol use, physical activity, or CVD itself. At least 1 study of disease outcomes has reported an increased risk of stroke among whites ≥65 years of age in neighborhoods with the lowest compared with those in neighborhoods with the highest socioeconomic status 21 ; 2 independent ecological studies suggest associations between aspects of neighborhood disadvantage and the risk of stroke 20,22 ; and several studies have shown a link between neighborhood disadvantage and an increased risk of CVD, often independently of adult individual-level socioeconomic status. [16][17][18] Several plausible mechanisms may link these 2 exposures with health.…”
Section: Discussionmentioning
confidence: 99%
“…Other longitudinal studies have documented similar association between neighborhood socioeconomic resources and myocardial infarction, stroke, coronary heart disease, and CVD mortality, in addition to a variety of CVD-related health factors such as BMI and blood pressure. [99][100][101][102][103] More recent studies have focused on moving beyond neighborhood socioeconomic disadvantage to an examination of specific features of neighborhood built/physical and social environments. Neighborhood built/physical environment indicators capture features of urban design and public spaces such as land use patterns, street connectivity, access to destinations and resources, and transportation systems.…”
Section: Residential Environmentsmentioning
confidence: 99%